Assessment of the potential effect of thermal effluents on CO2 absorption in coastal waters - Ko, Young Ho; Kim, Tae-Wook (Frontiers in Marine Science, 2024)
In recent decades, the cooling water discharge (CWD) from thermoelectric power plants into coastal waters has increased. The higher temperatures at the discharge outlets can elevate the seawater partial pressure of carbon dioxide (pCO2), potentially resulting in increased carbon dioxide (CO2) emissions or reduced CO2 absorption. Using a comprehensive global power plant database, we evaluated the impact of CWD on surface water CO2. Our assessment suggests that CWD from coastal power plants has the potential to contribute to a decline in oceanic CO2 uptake by 0.09–0.69 Tg C yr−1 (equivalent to 0.3–2.5 Tg CO2 yr−1). This estimation considered solely the influence of air–sea CO2 exchange, excluding the impact of air–sea heat exchange following cooling water discharge. Therefore, our estimate of 0.09–0.69 Tg C yr−1 is likely an upper theoretical limit. While our estimate appears minor in relation to global estimates of the oceanic CO2 flux, this impact of CWD should be addressed on a national scale. For precise quantification of the impact of CWD on local air–sea CO2 flux, accurate information on environmental factors such as wind speeds, mixed layer depth, and background carbonate chemistry is essential.